(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This article focuses on the development of lexical competence of future foreign language teachers in the process of professional training: reading literary texts, working with vocabulary, reading works rich in different plots, linguistic, grammatical, linguistic-cultural, stylistic, is devoted to the importance of the role of literary works, which are permanent custodians of socio-cultural information.